2021
DOI: 10.3390/pharmaceutics13101589
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Linear and Disulfide-Cyclized Ultrashort Cationic Lipopeptides Alone and in Combination with Fluconazole against Vulvovaginal Candida spp.

Abstract: Vulvovaginal candidiasis (VVC) occurs in over 75% of women at least once during their lifetime and is an infection that significantly affects their health. Candida strains resistant to standard azole antifungal therapy and relapses of VVC are more and more common. Hypothetically, biofilm is one of the main reasons of relapses and failure of the therapy. Ultrashort cationic lipopeptides (USCLs) exhibit high antimicrobial activities. Our previous study on USCLs revealed that disulfide cyclization can result in s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…In our previous work, we compared the antifungal activity of two pairs of cationic lipopeptides against Candida strains isolated from vulvovaginal candidiasis. These compounds effectively eradicated the mature structure of the biofilm [26]. In in vitro studies using polystyrene plates, we have demonstrated the advantage of the newly synthesized cyclic analogs C 16 -CKKKKC-NH 2 and C 16 -CKRKKC-NH 2 over their linear counterparts in the antimicrobial activity against Candida in planktonic and biofilm form [26].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In our previous work, we compared the antifungal activity of two pairs of cationic lipopeptides against Candida strains isolated from vulvovaginal candidiasis. These compounds effectively eradicated the mature structure of the biofilm [26]. In in vitro studies using polystyrene plates, we have demonstrated the advantage of the newly synthesized cyclic analogs C 16 -CKKKKC-NH 2 and C 16 -CKRKKC-NH 2 over their linear counterparts in the antimicrobial activity against Candida in planktonic and biofilm form [26].…”
Section: Introductionmentioning
confidence: 89%
“…These compounds effectively eradicated the mature structure of the biofilm [26]. In in vitro studies using polystyrene plates, we have demonstrated the advantage of the newly synthesized cyclic analogs C 16 -CKKKKC-NH 2 and C 16 -CKRKKC-NH 2 over their linear counterparts in the antimicrobial activity against Candida in planktonic and biofilm form [26]. At the same time, we have already proven that the use of combination therapy in the form of the simultaneous action of antifungal fluconazole that is conventionally used in VVC and the tested lipopeptides could be equally promising-this time indicating the advantage of the linear compounds C 16 -KKKK-NH 2 and C 16 -KRKK-NH 2 [26].…”
Section: Introductionmentioning
confidence: 99%
“…Other promising novel compounds like beta-glucan synthase inhibitor SCY-078, ion chelator DIBI, TOR inhibitor AZD8055, efflux modulators, and a group of novel antifungal chalcones have all proven highly synergistic against azole-resistant C. albicans, C. glabrata and other Candida species with reduced sensitivity to azoles [173,252,253,255,260]. A group of novel ultra-short cationic lipopeptides were not able to fully synergise with fluconazole, but did interact additively [259].…”
Section: Azole Synergy With Novel Compoundsmentioning
confidence: 99%
“…Other promising novel compounds like beta-glucan synthase inhibitor SCY-078, ion chelator DIBI, TOR inhibitor AZD8055, efflux modulators, and a group of novel antifungal chalcones have all proven highly synergistic against azole-resistant C. albicans, C. glabrata and other Candida species with reduced sensitivity to azoles [168,246,247,249,254]. A group of novel ultra-short cationic lipopeptides were not able to fully synergise with fluconazole, but did interact additively [253].…”
Section: Azole Synergy With Novel Compoundsmentioning
confidence: 99%